Demographic Revolution and Actual Demographic Situation in the World - Kačírek, Petr (Rewolucja demokratyczna i aktualna sytuacja demograficzna na świecie, 2010)
This contribution deals with the general questions of demographic development of the world. In the first part demographic revolution is characterized as a universal process that every population in the world undergoes. The following part of the contribution tries to define main tendencies and the state of current demographic situation in the world.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 110, s. 138-143